Correlation of Body Mass Index and Health to Quality of Life among Medical Undergraduates - Sivanesan Supramaniyam; Abdullah Firmansah; Ellyana Sungkar (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Overweight and obesity play a major role in an individual’s Health with Quality of Life (HRQOL). Several studies reported that there are differences between the results in different communities since HRQOL score in relation to BMI is sensitive to specific communities. The aim of this study was to investigate the relationship between the Body Mass Index (BMI) and Health with Quality of Life among the Medical Undergraduates of Universitas Padjadjaran, Bandung Methods: This study was an analytical cross-sectional study conducted from September to November 2012 in Faculty of Medicine Universitas Padjadjaran. A total of 280 respondents aged 16-30 were selected from the of 2009, 2010 2011 and 2012 classes of medical undergraduates after a thorough BMI screening. The overweight and obese subjects were selected using total sampling method, while subjects with normal BMI were sampled using simple random sampling. The subjects were asked to fill up Short Form 36 questionnaires. The correlation was assessed using Spearman`s Correlation test and the difference between the groups were analyzed using Kruskal-Wallis test. Results: Of the 260 respondents, there was a weak correlation between the BMI and total health with the quality of life of the undergraduates (rho = -0.173). Among the eight scales used, there was no correlation shown in three scales, namely body pain, social function, and mental health, in any of the groups. Conclusion: Increased body mass index impairs the health-related quality of life of the respondents, except in scales such as body pain, social function, and mental health.Keywords: Body mass index, health related to quality of life, Short Form 36 DOI: 10.15850/amj.v2n1.424